Successful Emulation of IV Decitabine Pharmacokinetics with an Oral Fixed-Dose Combination of the Oral Cytidine Deaminase Inhibitor (CDAi) E7727 with Oral Decitabine, in Subjects with Myelodysplastic Syndromes (MDS): Final Data of Phase 1 Study - Garcia-Manero, Guillermo; Odenike, Olatoyosi; Amrein, Philip C.; Steensma, David P.; DeZern, Amy E.; Michaelis, Laura C.; Faderl, Stefan; Kantarjian, Hagop M.; Lowder, James N.; Taverna, Pietro; Oganesian, Aram; Zhang, Xiaoping; et al. (Blood, 2016)
▪ Introduction: Patients with International Prognostic Scoring System (IPSS) intermediate 1 and 2 (Int) and high risk (HR) MDS benefit from therapy with hypomethylating agents (HMAs) decitabine (DAC) and azacitidine (AZA). Treatment requires 5 or 7 daily parenteral doses every month while the patient is benefitting. An oral HMA taken at home would provide patient convenience, and potentially enhance adherence to treatment particularly for long-term responders. Neither DAC nor AZA is readily bioavailable in oral form due to rapid clearance by cytidine deaminase (CDA) present in the gut and liver. E7727, a novel CDAi, is orally bioavailable with a large safety margin in preclinical models. We report here the final results of a Phase 1 study including an extension arm of a PK-guided first in human dose escalation trial of ASTX727 (the combination of oral DAC and E7727). Methods: Adult patients with Int or HR MDS or Chronic Myelomonocytic Leukemia (CMML) were enrolled in this dose-escalating trial. In addition to assessing the safety of the combination, the primary PK objective was to achieve a mean AUC of DAC following oral ASTX727 comparable to that achieved by IV DAC at the approved daily dose of 20 mg/m2. In the first cycle, each patient received an IV DAC dose of 20 mg/m2 on Day 1 as an internal comparator followed by oral ASTX727 on Days 2-5 escalated by cohort. Subsequent cycles were given with oral ASTX727 on Days 1-5 at the same dose of Cycle 1. Cycles were 28 days in length. Only one component at a time was escalated in each cohort and oral doses were not adjusted for weight or body surface area. Intrapatient dose escalation was permitted. Pharmacodynamics (PD) were evaluated by LINE-1 DNA methylation in peripheral blood. Responses were assessed using the International Working Group (IWG) criteria for response (Cheson et al, 2006). Results: 43 patients were treated in 5 cohorts of 6 patients each plus a 13 patient expansion of cohort 5. The median age was 71.5 years (range 59-86), 30/43 (70%) were male, and median time from diagnosis was 273 days (range 5-3518). Prior therapies had been administered to 22/43 (51%) patients including 20 who had received prior HMA. The AUC for IV DAC 20 mg/m2 in all patients (n=43) had a mean (CV) of 171(37%) ng*hr/mL. The Cmax for IV DAC 20 mg/m2 had a mean (CV) of 179(36%) ng/mL. Doses of each component of ASTX727 were escalated as shown in Table 1. E7727 was escalated first from 40 to 100 mg in cohorts 1 to 3 then kept constant at cohorts 4 to 6. DAC doses were kept constant at 20 mg in cohorts 1 to 3 then escalated to 40 mg at cohort 4 and de-escalated to 30 mg at cohort 5. Dose dependent increases in AUC and Cmax occurred with escalating doses. DAC AUC values after oral ASTX727 approached then exceeded IV at 149% by cohort 4. DAC Cmax values after oral ASTX727 never exceeded IV in any Cohort. Mean % LINE-1 demethylation on cycle 1 Day 8±SE increased with dose escalation reaching 12.8%±3.8 by cohort 4. Lower DAC AUC and Cmax were observed after lowering the oral DAC dose from 40 to 30 mg in cohort 5 as shown in Table 1. One patient in cohort 4 had a dose limiting toxicity of thrombocytopenia and no Grade ≥ 3 drug-related non-hematologic AEs were observed in any patient. The most common ≥ Grade 3 AEs regardless of relationship to the drug were thrombocytopenia (36%), anemia (30%), neutropenia (27%), and febrile neutropenia (21%). No drug-related Grade ≥ 3 gastrointestinal AEs were reported. A median of 5 cycles (range 1-23) were administered, 11 patients remain on therapy, and 14 (32%) have experienced objective clinical responses so far, including 5 Complete Response (CR), 4 marrow CR, and 5 Hematologic Improvement. Of 23 patients initially RBC dependent, 6 (26%), became independent and of 6 who were platelet dependent, 2(33%) became independent. Conclusions: ASTX727 (the combination of E7727 and DAC administered PO concomitantly) achieved the primary PK objective of emulating IV DAC 20 mg/m2 AUC levels with a similar safety profile. Day 8 LINE-1 demethylation in Cohort 4, overall clinical response and transfusion independence rates are consistent with those historically reported following DAC 20 mg/m2 IV for 5 days, even though 47% had received prior HMA therapy. ASTX727 has now proceeded to a randomized phase 2 study comparing IV DAC 20 mg/m2 IV daily for 5 days to oral ASTX727 at the doses of 35 mg DAC and 100 mg E7727 daily for 5 days in Int or HR MDS and CMML patients. [Display omitted] Odenike:Geron: Research Funding; Suneisis: Honoraria, Membership on an entity's Board of Directors or advisory committees; Incyte: Honoraria, Membership on an entity's Board of Directors or advisory committees; CTI/Baxter: Honoraria, Membership on an entity's Board of Directors or advisory committees; Sanofi-Aventis: Honoraria, Membership on an entity's Board of Directors or advisory committees; Spectrum: Honoraria, Membership on an entity's Board of Directors or advisory committees; Algeta: Honoraria, Membership on an entity's Board of Directors or advisory committees. Steensma:Amgen: Consultancy; Celgene: Consultancy; Janssen: Consultancy; Ariad: Equity Ownership; Genoptix: Consultancy; Millenium/Takeda: Consultancy. Michaelis:Incyte: Honoraria; Pfizer: Equity Ownership; Celgene: Honoraria, Speakers Bureau. Lowder:Astex Pharmaceuticals, Inc.: Employment. Taverna:Astex Pharmaceuticals: Employment. Oganesian:Astex Pharmaceuticals, Inc.: Employment. Zhang:Astex Pharmaceuticals, Inc.: Employment. Azab:Astex Pharmaceuticals, Inc.: Employment. Savona:Ariad: Membership on an entity's Board of Directors or advisory committees; Amgen Inc.: Membership on an entity's Board of Directors or advisory committees; TG Therapeutics: Research Funding; Sunesis: Research Funding; Celgene: Membership on an entity's Board of Directors or advisory committees; Takeda: Research Funding; Gilead: Membership on an entity's Board of Directors or advisory committees; Incyte: Membership on an entity's Board of Directors or advisory committees, Research Funding.